Adverse events following Pfizer-BioNTec vaccine against COVID-19 in population more than 12 years of age, Nepal - Devbhandari, Ranjan; Bajracharya, Sumana; Aryal, Sushant; Rajbhandari, Piyush; Shakya, Tripti; Gupta, Mayuri; Tuladhar, Shreyashi; Shakya, Binnam; Shrestha, Ashis (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Pfizer-BioNTec vaccine was started in Nepal for the age group of more than 12 y. This study was conducted to find out the adverse event following immunization with Pfizer-BioNTech vaccine against COVID-19 at Patan Academy of Health Sciences (PAHS). Method: This is a descriptive study conducted at PAHS from November to December 2021. The vaccine recipients were called over the phone after 72 h of receiving the vaccine to find out adverse events following immunization (AEFI). They were inquired about the list of pre-defined AEFI. Ethical approval was obtained. Result: A total of 1377(27.4%) individuals among 5014 receiving the first dose and 983(71.4%) of 1377 receiving the second dose were enrolled in the study. Vaccine recipients who had minor AEFI in the first dose were 462(33.6%) and in the second dose were 205(20.9%). Reported AEFI in both first and second dose was pain 377(27.4%) and 97(9.9%) respectively, followed by fever in 65(4.8%) and 91(9.3%) respectively. There were no severe AEFI reported in both doses of vaccination. The AEFI started within 24 h and subsided within 72 h. Conclusion: Minor AEFI of pain and fever was reported with the first and second dose of the Pfizer-BioNTech vaccine. There were no severe and serious AEFI reported in this study population.